PRAKTIK KLONING MANUSIA DALAM PERSPEKTIF ETIKA TELEOLOGIS-UTILITARIANISME - , YOSEF ADICITA; , Dra. Jirzanah, M. Hum ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The practice of cloning is considered the most inhumane and violate various aspects of life in society. The literature relating to the practice of cloning for the danger to be studied in the world of health and only very rarely that discusses the practice of cloning according to the perspective of a philosophical theory, the authors feel this research is very important to resolve. The author in this study attempted to discuss the various polemics generated by cloning practices in teleological-utilitarianismperspective. problems which the author adopted in this study is about ethical issues in the practice of cloning, how teleological-utilitarianism ethical doctrine talk about, which then see how teleological-utilitarianismethics in view of the practice of cloning. The study titled \"Practice Cloning According view Teleological- UtilitarianismEthics\" using methodological philosophical hermeneutics. Sources of key data used is through the study of literature with the main book \"Ethical Problems of Human Cloning\" by C.B. Kusmaryanto . Another source of support is taken from the latest articles and news related to the practice of cloning and ethical teachings of utilitarianism. This study also uses elements of historical continuity method, analysis, description, interpretation and hermeneutics, in order to collect and sort all kinds of information and development of the practice of cloning and to explain the relevance and influence on human morality. The results achieved in this study were1) Obtain a description of the ethical issues in the practice of cloning which include